Fathers' Experiences of Caring for a Child with a Chronic Illness: A Systematic Review - Shelley Spurr; Cynthia A. Danford; Karyn J. Roberts; Debbie Sheppard-LeMoine; Fernanda Machado Silva-Rodrigues; Michelle Darezzo Rodrigues Nunes; Leslie Darmofal; Anne L. Ersig; Mandie Foster; Barbara Giambra; Stacee Lerret; Michele Polfuss; et al. (MDPI AG, 2023)
The prevalence of children living with chronic health conditions is increasing worldwide and can disrupt family roles, relationships, function, and parental involvement in family caregiving. The purpose of this systematic review was to explore fathers' experiences and involvement in caring for a child with a chronic condition. Systematic searches using seven databases were conducted. Study criteria included (1) peer-reviewed original research in English, Spanish, French, or Portuguese, (2) children less than 19 years of age with a chronic condition, (3) fathers (biological or guardian) as direct informants, and (4) outcomes addressing fathers' experience, perceptions, and/or involvement in the child's care. Data were synthesized from ten articles reflecting eight separate studies that utilized quantitative designs. Three areas of focus were identified: Family Functioning, Father's Psychological Health, and Need for Support. Data suggested increased involvement from the father in caring for their child with a chronic condition was associated with improved family functioning, increased anxiety and distress, decreased self-esteem, and increased need for support. This review revealed a paucity of data regarding fathers' experiences and involvement when caring for a child with a chronic condition, with that available primarily from developed countries. Rigorous empirical studies are needed to deepen understanding of how fathers are involved in the care of their child with a chronic condition.